Cardiomyocyte Senescence and Cellular Communications Within Myocardial Microenvironments - Tang, Xiaoqiang; Li, Pei-Heng; Chen, Hou-Zao (Frontiers in Endocrinology, 2020)
Cardiovascular diseases have become the leading cause of human death. Aging is an independent risk factor for cardiovascular diseases. Cardiac aging is associated with maladaptation of cellular metabolism, dysfunction (or senescence) of cardiomyocytes, a decrease in angiogenesis, and an increase in tissue scarring (fibrosis). These events eventually lead to cardiac remodeling and failure. Senescent cardiomyocytes show the hallmarks of DNA damage, endoplasmic reticulum stress, mitochondria dysfunction, contractile dysfunction, hypertrophic growth, and senescence-associated secreting phenotype (SASP). Metabolism within cardiomyocytes is essential not only to fuel the pump function of the heart but to maintain the functional homeostasis and participate in the senescence of cardiomyocytes. The senescence of cardiomyocyte is also regulated by the nonmyocytes (endothelial cells, fibroblasts, and immune cells) in the local microenvironment. On the other hand, the senescent cardiomyocytes alter their phenotypes and subsequently affect the nonmyocytes in the local microenvironment and contribute to cardiac aging and pathological remodeling. In this review, we first summarized the hallmarks of the senescence of cardiomyocytes. Then, we discussed the metabolic switch within senescent cardiomyocytes and provided a discussion of the cellular communications between dysfunctional cardiomyocytes and nonmyocytes in the local microenvironment. We also addressed the functions of metabolic regulators within nonmyocytes in modulating myocardial microenvironment. Finally, we pointed out some interesting and important questions that are needed to be addressed by further studies.